The Complexities of Metal Detecting Policy and Practice: A Response to Samuel Hardy, ‘Quantitative Analysis of Open-Source Data on Metal Detecting for Cultural Property’ (Cogent Social Sciences 3, 2017) - Deckers Pieterjan; Dobat Andres; Ferguson Natasha; Heeren Stijn; Lewis Michael; Thomas Suzie (Open Archaeology, 2018)
In his paper ‘Quantitative analysis of open-source data on metal detecting for cultural property’, Samuel Hardy suggested that permissive policy is ineffective in minimizing the damage done to cultural heritage by non-professional metal detecting. This response paper contests the basic assumptions upon which this analysis is based. While Hardy‘s comparative, quantitative approach is laudable, it is founded in a biased and simplistic outlook on the metal detecting phenomenon.